Cognitive Factors in Mathematical Skill Acquisition in Primary School Children with ASD - Pereverzeva, D.S.; Mamokhina, U.A.; Ilyunceva, A.A.; Uskova, O.A. (Sovremennaâ Zarubežnaâ Psihologiâ, 2025)
Difficulties in mastering mathematics are among the typical problems of school education for children with autism spectrum disorders (ASD). In this regard, the study of factors influencing the development of mathematical skills in children with ASD is of particular relevance. This review examines the role of key cognitive processes associated with the development of mathematical skills: visual-spatial abilities, executive functions, as well as symbolic and non-symbolic numerical magnitude processing skills. Analysis of the literature indicates that in children with ASD, executive functions and number processing are typically less developed compared to typical development. Visual-spatial abilities show high variability: a subgroup can be identified among children with ASD characterized by a cognitive profile with a peak in visual-spatial abilities. However, this profile is not universal, which complicates definitive comparative conclusions. It has been established that these cognitive factors, as in the norm, are positively associated with mathematical achievement in ASD. At the same time, the strength of these relationships and the interaction of the factors differ from those observed in typical development. The practical significance of this review lies in the fact that understanding the specifics of cognitive factors in mathematical development in ASD can contribute to the development of more effective teaching and intervention strategies. Трудности в овладении математикой относятся к числу типичных проблем школьного обучения детей с расстройствами аутистического спектра (РАС). В связи с этим особую актуальность приобретает изучение факторов, влияющих на формирование математических навыков у детей с РАС. В данном обзоре рассматривается роль ключевых когнитивных процессов, ассоциированных с развитием математических навыков: зрительно-пространственных способностей, исполнительных функций, а также навыков символической и несимволической обработки числовой величины. Анализ литературы свидетельствует, что у детей с РАС исполнительные функции и обработка чисел, как правило, развиты слабее, чем при типичном развитии. Зрительно-пространственные способности демонстрируют высокую вариативность: среди детей с РАС может быть выделена подгруппа, для которой характерен когнитивный профиль с пиком на зрительно-пространственных способностях. Однако такой профиль не является универсальным, что затрудняет однозначные сравнительные выводы. Установлено, что перечисленные когнитивные факторы, как и в норме, положительно связаны с математическими достижениями при РАС. При этом сила связей и взаимодействие факторов отличаются от аналогичных показателей при типичном развитии. Практическая значимость данного обзора заключается в том, что понимание специфики когнитивных факторов математического развития при РАС может способствовать разработке более эффективных стратегий обучения и коррекции.